Agile Methodologies as Drivers of Organizational Culture in Digital Transformation Projects - Murudi, Tendamudzimu; Khoza, Thulani Lucas (Journal of Information System and Informatics, 2025)
Organisations are increasingly adopting agile methodologies to accelerate digital transformation, yet outcomes remain inconsistent when agile is viewed solely as a delivery technique rather than a cultural mechanism. This study explores how agile practices influence organisational culture during transformation and identifies the conditions under which benefits are realised. Using an explanatory mixed-methods design, the study combined a survey (N = 315) with 18 semi-structured interviews. After ensuring scale reliability, bivariate correlations and linear/multiple regressions were conducted in IBM SPSS, while interview transcripts were thematically coded to explain the quantitative findings. Agile practices were positively linked to a supportive culture (Pearson r ≈ .32), with simple regression indicating that agile significantly predicted culture (R² ≈ 0.10). A multiple regression predicting digital-transformation outcomes from agile and culture revealed a significant model (R² ≈ 0.40), where agile was the stronger predictor and culture made a smaller yet meaningful contribution. Qualitative insights highlighted how cadence, visibility, and iteration normalised collaboration, transparency, and rapid feedback. Practically, managers should focus on culture outcomes in agile roadmaps, institutionalise essential routines, and reduce structural hand-offs for sustained transformation.